The Empowerment Of Rancakalong Village In The Development Of Culture-Based Tourism Villages - Kurniawan, Wawan; Anwar; Canra Permadi (SAMPURASUN, 2023)
Villages are now no longer seen as an area that only depends on the regional government, but villages are now self-governing communities where the Village Law states that villages have a function in managing government, village finances, village development, and obtaining facilities. and guidance from the Regency/City government. Building a village is not something easy. Development requires participation from all elements of village society. Village development does not only focus on physical development, but village development also includes economic development and social development. Development in an area or village is an inevitability that must be carried out by regional governments and village governments, one of which is through development that has beneficial value for regional governments, village governments and the community. Developing tourism is the most appropriate step taken by regional governments and village governments where tourism is an important aspect for a country and regional government. With tourism, a country or more specifically the local government where tourist attractions are located provides benefits to the welfare of the community and becomes a source of development costs for government administrators. Empowerment and development of an area or village of course needs to be supported by the entire community, through community empowerment in developing an area. The research method used by researchers is descriptive analysis using a qualitative approach. Qualitative research is scientific research that aims to understand a phenomenon in a social context naturally by embedding a process of in-depth communication interaction between research and the phenomenon being studied. This approach was chosen with the consideration that the nature of research data is able to maintain the integrity of the object, meaning that various data related to research are understood as an integrated unit.